The Efficiency of Game-Based Learning Towards Student’s Focus And Enjoyment Using Board Game : A Case Study at SK Martin - Jonathan, Sidi; Syahrul Nizam, Bin Junaini; Edwin, Mit; Jacey Lynn, Minoi (UNIMAS Publisher, 2019)
To observe and evaluate how the implementation of gamebased learning can improve students’ focus in class and at the same time having fun with their study.